The Generational Welfare Contract: Justice, Institutions and Outcomes Changing Generational Welfare Contracts: Just Institutions and Outcomes - Kenneth Nelson (Edward Elgar Publishing, 2017)
This groundbreaking book brings together perspectives from political philosophy and comparative social policy to discuss generational justice. Contributing new insights about the preconditions for designing sustainable, inclusive policies for all of society, the authors expose the possibilities of supporting egalitarian principles in an ageing society through balanced generational welfare contracts. Welfare states are largely structured around social risks that appear in distinct phases of human life, including childhood, working age and old age. By empirically analysing the causes and consequences of social policy in a large number of countries, the authors show that balanced generational welfare contracts - in which age-related social protection is more evenly distributed across different stages of life - is to the advantage of all age groups, therefore contributing to social justice and welfare state sustainability. The authors offer a combination of descriptive data analysis and statistical regressions to provide robust evidence that countries can avoid generational trade-offs in policymaking and find positive-sum solutions.